The Influence of Incentives and Employee Satisfaction Performance Against Job Loyalty at PT.XYZ - Putri Carolyn Panggabean (Institute of Computer Science (IOCS), 2020)
PT XYZ (CMSS) is a subsidiary of PT Catur Sentosa Adiprana (CSA) which is engaged in the distribution of building materials - giving birth to the concept of building material shopping under one roof in Indonesia under the name Mitra10. As an anticipation step towards the era of globalization and the free market of AFTA in 2003, where all Asian countries can do business freely in member countries such as in their own countries, then entering the retail business is felt important to strengthen networks, survive, and develop even more rapidly. So that researchers are interested in examining the incentives and performance satisfaction of work loyalty at PT XYZ Medan. So we get a few conclusions from this study. The incentive variable partially has a positive and significant effect on employee work loyalty at PT XYZ Medan. This is seen through the t-incentive value of 3.714 which is greater than the t-table value of 2.051 and also has a significant t level of 0.001 smaller than alpha 0.05. So the alternative hypothesis related to the variable is accepted. The performance satisfaction variable partially has a positive and significant effect on employee work loyalty at PT XYZ Medan. This is seen through the t-incentive value of 3.222 which is greater than the t-table value of 2.051 and also has a significant level of t of 0.003 smaller than alpha 0.05. So the alternative hypothesis related to the variable is accepted. The incentive and performance satisfaction variables jointly influence work loyalty at PT XYZ Medan. This can be seen through the value of F-count = 16.126 and the significance (p-value) = 0.000, it can be concluded that the F-count (16.126) is greater than the F-table (2.95) and the p-value (0.001) is smaller than sig-α = (0.05).